Feasibility and acceptability of a midwife-led health education strategy to reduce exposure to biomass smoke among pregnant women in Uganda, A FRESH AIR project. Issue 12 (2nd December 2019) - Nantanda, Rebecca; Buteme, Shamim; van Kampen, Sanne; Cartwright, Lucy; Pooler, Jill; Barton, Andy; Callaghan, Lynne; Mirembe, Jean; Ndeezi, Grace; Tumwine, James K.; Kirenga, Bruce; Jones, Rupert
ABSTRACT: Biomass smoke exposure is a threat to child and maternal health in many resource-limited countries and is associated with poor pregnancy outcomes and serious lung diseases in the offspring. We aimed to assess the feasibility, acceptability and impact of a midwife-led education programme on biomass risks and prevention for women attending maternity clinics in Uganda. Education materials were co-developed through an iterative process by midwives and other stakeholders. The materials were serially tested and approved by the Ministry of Health and used by midwives and village health teams (VHTs). The district health team, 12 midwives and 40 VHTs were sensitised on biomass smoke. Two hundred and forty-four women were educated about biomass smoke by midwives; pre- and post-session questionnaires showed major improvements in knowledge of biomass smoke risks. Qualitative interviews with women three months after the sessions showed that they made behavioural changes such as avoiding smoke while cooking, using dry wood, solar power for lighting and improved ventilation. The major barrier to behavioural changes was poverty, but some improvements cost no money. The programme delivered by midwives was feasible and acceptable; implementing this programme has the potential to reduce exposure to smoke with major benefits to mother, foetus, and children throughout their lives.